Machine learning made easy with R : An intuitive step by step blueprint for beginners - Lewis N.D (USA [s.n], 2017)
Machine Learning Made Easy with R offers a practical tutorial that uses hands-on examples to step through real-world applications using clear and practical case studies. Through this process it takes you on a gentle, fun and unhurried journey to creating machine learning models with R. Whether you are new to data science or a veteran, this book offers a powerful set of tools for quickly and easily gaining insight from your data using R.
Keywords: Khoa học cơ bản